ARTIFICIAL INTELLIGENCE AND ACCOUNTANTS’ WORK EFFICIENCY: A GLOBAL BIBLIOMETRIC AND SCIENCE-MAPPING ANALYSIS OF ACCOUNTING RESEARCH - Noldin Jerry Tumbel (Smart Education, 2026)
Abstract: This study maps the intellectual, conceptual, and temporal structure of research on artificial intelligence (AI) and accountants’ work efficiency. Design/methodology/approach — A Scopus search identified 1,418 English-language, open-access journal articles published from 2020 to 2026. Because the term “account” generated finance- and banking-related noise, title and author-keyword screening retained 185 accounting- and audit-relevant articles. Performance analysis was combined with keyword co-occurrence, network, overlay, and density mapping using VOSviewer-compatible files. Findings — Annual output increased from 3 articles in 2020 to 67 in 2025, with 39 additional articles indexed during the partial 2026 period. The corpus comprised 91 sources and 520 authors, with a mean of 14.0 citations per article and a median of 3. The keyword network contained 35 terms, 70 links, and five clusters covering audit and risk analytics; professional automation and ethics; generative AI, financial reporting, and governance; digital infrastructure; and education and technology acceptance. The thematic focus shifted from RPA, blockchain, and IoT toward generative AI, large language models, explainable AI, corporate governance, and financial reporting. Originality/value — This study provides an outcome-centered and reproducible map of AI-enabled accounting efficiency, distinguishes established automation themes from emerging generative-AI and governance research, and documents the screening required to address query contamination. Keywords: artificial intelligence; accounting; work efficiency; bibliometric analysis; science mapping. Abstrak: Studi ini memetakan struktur intelektual, konseptual, dan temporal dari penelitian mengenai kecerdasan buatan (AI) dan efisiensi kerja akuntan. Desain/metodologi/pendekatan — Pencarian di Scopus mengidentifikasi 1.418 artikel jurnal akses terbuka berbahasa Inggris yang diterbitkan antara tahun 2020 dan 2026. Karena istilah